Mass Media – A Starting Point for Solving EU’s Lack of Democratic Legitimacy - Laura-Mariana Paraschiv; Monica-Florina Gherghel (Romanian Journal of Communications and Public Relations, 2023)
European identity is seen by many communication scholars as a potential solution for the EU’s lack of legitimacy. At the same time, the existence of a European public sphere is a prerequisite for the process of shaping a sense of belonging among European citizens which would eventually produce a common European identity. In creating a European public sphere, mass media play a central role as they make people aware of their common European rights, values and solutions and they orientate individuals towards feeling united in solving common problems and accomplishing common missions. The present article elaborates from a theoretical perspective on this complex cycle of European identity production (mass media, European public sphere, European identity) that should lead to solving EU’s democratic legitimacy deficits. First, the focus is on mass media’s role in telling European citizens what to think of and talk about in order to develop a sense of belonging to the wider European community. Second, the article discusses about mass media’s power to increase or decrease public support for the EU, that the European public sphere needs in order to sustain the emergence of a European identity, by using positively or negatively valenced news frames in evaluating EU issues.